(untitled) (Medico Legal Update, 2021)
Background: Cervical cancer is the second leading cause of cancer deaths in low and middle-income countries. The International Agency for Research on Cancer (IARC) gauges that the frequency of cervical disease will increment by 75% worldwide by 2030. Method: This descriptive correlational study was carried out to examine women’s readiness to perform Pap smear test. to (1) assess women’s readiness to perform Pap Smear test, (2) identify the association between woman’s age, family’s socioeconomic status, gravidity, parity, abortion, and their Stages of Change for conducting Pap Smear test, the Perceived Susceptibility to contract cervical cancer, the Perceived Seriousness of cervical cancer, the Perceived Barriers to conduct Pap Smear test, the Perceived Benefits of conducting Pap Smear Test, and the Health Motivation to conducting Pap Smear Test, and (3) investigate the differences in the Perceived Susceptibility to contract cervical cancer, the Perceived Seriousness of cervical cancer, the Perceived Barriers to conduct Pap Smear test, the Perceived Benefits of conducting Pap Smear Test, and the Health Motivation to conducting Pap Smear Test between the groups of the Stages of Change for conducting Pap Smear test woman’s level of education, family’s socioeconomic class, and family type. Results: The target population of this study was selected from adult, married women on social media. The SR used a self-reported online survey for data collection. The SR prepared the online survey and published its link on the social media pages and groups, where the study objectives were demonstrated to study subjects Conclusion: Most of the women are precontemplators. The older the age, the greater the Susceptibility to contracting cervical cancer and the better the family’s socioeconomic status, the greater the greater Susceptibility to contracting cervical cancer.